C-Reactive Protein Causes Blood Pressure Drop in Rabbits and Induces Intracellular Calcium Signaling - Bock, Christopher; Vogt, Birgit; Mattecka, Stephan; Yapici, Gülcan; Brunner, Patrizia; Fimpel, Sandra; Unger, Juliane K.; Sheriff, Ahmed (Frontiers in Immunology, 2020)
Systemic diseases characterized by elevated levels of C-reactive protein (CRP), such as sepsis or systemic inflammatory response syndrome, are usually associated with hardly controllable haemodynamic instability. We therefore investigated whether CRP itself influences blood pressure and heart rate. Immediately after intravenous injection of purified human CRP (3.5 mg CRP/kg body weight) into anesthetized rabbits, blood pressure dropped critically in all animals, while control animals injected with bovine serum albumin showed no response. Heart rate did not change in either group. Approaching this impact on a cellular level, we investigated the effect of CRP in cell lines expressing adrenoceptors (CHO-α1A and DU-145). CRP caused a Ca2+ signaling being dependent on the CRP dose. After complete activation of the adrenoceptors by agonists, CRP caused additional intracellular Ca2+ mobilization. We assume that CRP interacts with hitherto unknown structures on the surface of vital cells and thus interferes with the desensitization of adrenoceptors.